Pengembangan Game Erfina sebagai Media Pembelajaran Ekosistem : (Penelitian Pengembangan di Kelas VII SMP Negeri 02 Satu Atap Suwawa Selatan) - Oktaviani Rajalawo; Abubakar Sidik Katili; Marini Susanti Hamidun; Elya Nusantari; Ani M. Hasan; Ramli Utina (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
This study aims to develop erfina game as ecosystem learning media and to know and describe the results of expert validation, teacher responses, student responses and student learning outcomes of the developed media. This research uses the research and development method (Research & Development). The model used in this research is ADDIE consisting of 3 stages, namely Analysis, Design, and Development. The trial was conducted on 10 students of Class VII of SMP Negeri 02 Satu Atap Suwawa Selatan. The results of the study found: (1) validity test based on the percentage of media validation of 85% (Very Valid) and material expert validation obtained a percentage of 87% (Very Valid). (2) Practicality test based on teacher response results obtained a percentage of 91% (Very Practical) and the results of students' responses of 93% (Very Practical). (3) Student learning outcomes test obtained from the results of student learning tests through Preetest and Posttest evaluations, based on the N-Gain scale obtained a value of 0.53 or 53% which is included in the moderate category